2015
DOI: 10.4258/hir.2015.21.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year Experience with Telemedicine Services in Gangwon Province in Korea

Abstract: Objectives This study attempted to identify the factors that contribute to successful telemedicine service. This was done by analyzing the operational state of successful telemedicine services offered in Gangwon Province of Korea and their outcome for the last fifteen years. Methods A comparative analysis was made based on reports and a thesis on the satisfaction rate of patients and providers, patient compliance to treatment, and economic assessment of Gangwon telemedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Another barrier frequently highlighted in the literature was the complexity of technologies (n=5) [30,39,40,43,46]. Frequent technical issues coupled with inadequate onsite support to resolve them were cited as reasons for discontinuing engagement with DHTs (n=2) [34,39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another barrier frequently highlighted in the literature was the complexity of technologies (n=5) [30,39,40,43,46]. Frequent technical issues coupled with inadequate onsite support to resolve them were cited as reasons for discontinuing engagement with DHTs (n=2) [34,39].…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, patients questioned the accuracy of the measurements and data recorded (BP readings) by DHTs [19,43,47].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [21] designed a randomized controlled trial and showed a higher compliance for patients with esophageal cancer using Internet follow-up after radiotherapy compared to a control group. A 15-year experience with telemedicine in Korea published by Kim et al [22] compared telemedical services for patients versus face-to-face medical service and showed a significant improvement of compliance in drug administration and lifestyle changes. However, HCPs also named certain disadvantages regarding telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization definition of telemedicine is the delivery of health care services, wherein distance is a critical factor, by all health care professionals using information and communication technologies for the exchange of valid information for the diagnosis, treatment, and prevention of diseases and injuries, research and evaluation, and for the continuing education of health care providers, all in the interest of advancing the health of individuals and their communities [7]. Previous research has confirmed the advantages of telemedicine, such as saving traveling time and reducing medical expenses [8,9], increasing patient satisfaction [9,10], effectiveness comparable to hospital face-to-face consultation [11], and improved management of chronic diseases such as diabetes and hypertension [8,12]. However, the effectiveness of telemedicine for the distribution of medical resources in rural China remains unclear.…”
Section: Introductionmentioning
confidence: 99%